Test performance of PET-CT for mediastinal lymph node staging of pulmonary carcinoid tumours. Issue 4 (14th August 2014) - Pattenden, Holly A; Leung, Maria; Beddow, Emma; Dusmet, Michael; Nicholson, Andrew G; Shackcloth, Michael; Mohamed, Saifullah; Darr, Adnan; Naidu, Babu; Iyer, Swetha; Marchbank, Adrian; Greenwood, Amy; et al.
Abstract : Positron emission tomography-CT (PET-CT) is one of the initial mediastinal staging modality for non-small cell lung cancer; however, the clinical utility in carcinoid tumours is uncertain. We sought to determine the test performance of PET-CT for mediastinal lymph node staging of pulmonary carcinoid tumours. We collated data from seven institutions, performing a retrospective search on pathological databases for a consecutive series of patients who underwent thoracic surgery (with lymph nodal dissection) for carcinoid tumours with preoperative PET-CT staging. PET-CT results were compared with the reference standard of pathologic results obtained from lymph node dissection and test performance reported using sensitivity and specificity. From November 1999 to January 2013, 247 patients from seven institutions underwent surgery for carcinoid tumours with a corresponding preoperative PET-CT scan. The mean age of the patients was 61 (SD 15, range 73) and 84 were male patients (34%). The pathologic subtype was typical carcinoid in 217 patients (88%) and atypical carcinoid in 30 patients (12%). Results from lymph node dissection were obtained in 207 patients. The calculated sensitivity and specificity of PET-CT to identify mediastinal lymph node disease was 33% (95% CI 4% to 78%) and 94% (95% CI 89% to 97%), respectively. Our results indicate that PET-CT has a poor sensitivity but good specificity to detect the presence of mediastinal lymph node metastases in pulmonary carcinoid tumours. Mediastinal lymph node metastases cannot be ruled out with negative PET-CT uptake, and if the absence of mediastinal lymph node disease is a prerequisite for directing management, tissue sampling should be undertaken.